On increasing the order and density of 3D finite element meshes - Wong, S. M. (2014)
A simple procedure is suggested to increase the order of 3D finite element meshes. The method suggested can be applied to any 3D finite element mesh containing different commonly used 3D element types such as tetrahedron, pyramid, prism and hexahedron. Based on the element order increasing scheme, an element subdivision scheme is also proposed to carry out uniform refinement for general 3D meshes. Detailed timings indicate that the computational time needed to increase the order and density of the mesh is proportional to the number of elements generated.